TEACHERS' PERCEPTIONS OF THE USE OF THE TALKING CHIPS METHOD TO IMPROVE THE SPEAKING SKILLS OF ELEMENTARY SCHOOL STUDENTS - Dewi Ayu Larassati; Robiatul Munajah (Journal of Practice Learning and Educational Development, 2026)
Education is a necessity for every Indonesian citizen aimed at forming a child to become the nation's successor and be able to face developments in various fields. Educational institutions need to innovate to organize teaching and learning activities that aim for students to gain knowledge to improve their potential and skills. Speaking skills are a skill that needs to be applied to all students so that they are able to convey ideas but by conveying them using language verbally, other people are able to understand what is said by students. Talking chips is a learning model so that students are able to interact in a group, channel ideas, concepts that they want to express. So that they are able to create ideas about what they want to express to improve speaking skills. By using the Classroom Action Research (CAR) method or (action research). The results of this study indicate that the application of the Talking Chips method will increase the level of student confidence so that they are able to increase insight or increase the level of speaking skills. This shows with a percentage level of 80% that the Talking Chips method affects students' confidence in speaking skills.